Anti-mitochondria antibody-related tubulointerstitial nephritis accompanied by severe hypokalemic paralysis - Morita, Masashi (CEN Case Rep, 2019)
A 47-year-old man presented with severe hypokalemic paralysis and respiratory failure. A large amount of potassium was administered along with providing intensive care, and his condition improved. Hypokalemia was attributed to increased urinary potassium excretion. A kidney biopsy was performed to make a definitive histological diagnosis. It revealed acute tubulointerstitial nephritis (TIN). After the diagnosis, prednisolone was administered, and the TIN gradually improved. From the clinical course and laboratory findings, the TIN was presumed to be an autoimmune disorder. Further specific autoantibody tests were positive for anti-mitochondrial antibody (AMA), which has been gaining increasing attention in regard to TIN. In addition, all previous cases of TIN associated with AMA have affected females. The detailed pathogenetic mechanisms are as yet unclear and require further investigation.